Literature Review: Improving The Quality of Hospital Services through The Utilization of Electronic Nursing Documentation - Rahma, Rahmawati Sri Utami; Andriyanto, Arief (STIKes Patria Husada Blitar, 2024)
Documentation of nursing care from assessment to evaluation in the patient's medical record is very important because it is legal evidence of a case, an important indicator of the quality of patient care, and a tool for assessing the quality of service as well as being an important element of clinical documentation and quality, effective medical services. Efforts that can be made to improve service quality are through changes in electronic-based documentation. The purpose of this literature review was to get an idea of whether electronic nursing documentation can be effective in improving the quality of service and the quality of nursing documentation in hospitals. The database search included Google Scholar getting 18 articles, ProQuest getting 78 articles, Pubmed getting 15 articles, National Library getting 7 articles. The keyword used in the article search was electronic nursing documentation and only 5 articles were used which were suitable through analysis of objectives, suitability of topics, research methods used, sample size, research ethics, results of each article, and limitations that occurred. There results were android-based documentation of nursing diagnoses and interventions was effective in improving the quality of documentation of nursing diagnoses and interventions and the quality of hospital services.